FRI0036 What is the Level of Agreement Between Disease Activity Indices and Response Criteria Among Rheumatoid Arthritis Patients Treated with TNF Inhibitors?. (9th June 2015) - Keystone, E.; Baer, P.; Avina-Zubieta, A.; Jaroszynska, A.; Rodrigues, J.; Arendse, R.; Sholter, D.; Starr, M.; Masetto, A.; Sampalis, J.; Rampakakis, E.; Tkaczyk, C.; et al.
Abstract : Background: Several standardized response criteria and disease activity indices are used to assess treatment efficacy in rheumatoid arthritis (RA). These measures comprise different types and number of variables resulting in different weighting of individual variables within each of them. Objectives: The aim of this analysis was to compare the performance of ACR, SDAI major and minor, and HAQ response criteria and to determine their level of agreement with the DAS28, SDAI, and CDAI definitions of low disease activity (LDA) and remission in RA patients treated with infliximab (IFX) or golimumab (GLM) in a real-world, Canadian, clinical practice setting. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, AS, or PsA with IFX or GLM. The analysis was based on RA patients treated with IFX between 2002-2014 or GLM between 2010-2014. Response was assessed with ACR20, ACR50, ACR70, HAQ improvement of 0.22 and 0.5, SDAI major (≥22) and minor improvement (≥10). Disease state was assessed with DAS28, SDAI, and CDAI definitions of LDA (<3.2, ≤11, ≤10, respectively) and remission (<2.6, ≤3.3, ≤2.8, respectively). The level of agreement was assessed with the proportion of concordant pairs over the total number of cases in each cross-tabulation and the Kappa statistic. Results: A total of 830 RA patients with 4, 100 available observations were included. The criteria for each definition of response/disease state were met for the following proportion of cases: ACR20 (66.4%), ACR50 (44.5%), ACR70 (26.4%), ΔHAQ≥0.22 (65.5%), ΔHAQ≥0.5 (53.4%), SDAI major improvement (55.8%), SDAI minor improvement (80.8%), DAS28 remission (29.4%), CDAI remission (20.4%), SDAI remission (21.8%), CDAI LDA (57.5%), SDAI LDA (58.1%), and DAS28-ESR LDA (46.0%). Statistically significant (Kappa P<0.001) associations were observed for all combinations of variables examined. Overall, the ACR response criteria performed better than the HAQ and SDAI response criteria in their agreement with LDA and remission. In general, higher levels of response in all three measures (ACR20 vs. ACR50 vs. ACR70; ΔHAQ≥0.22 vs. ΔHAQ≥0.5; SDAI minor vs. major) showed better agreement with LDA and remission. The highest level of agreement between response criteria and disease state was observed between the strictest definitions, namely between ACR70 and CDAI/SDAI remission; whereas, SDAI minor improvement showed the lowest level of agreement with remission, irrespective of definition. Conclusions: This analysis showed that significant variation exists in the agreement between the various efficacy outcome measures. Thus, the choice of outcome measure used to make treatment decisions could have a significant impact on patient management. Disclosure of Interest: E. Keystone Consultant for: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, Speakers bureau: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, P. Baer Consultant for: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, Speakers bureau: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, A. Avina-Zubieta: None declared, A. Jaroszynska: None declared, J. Rodrigues: None declared, R. Arendse Consultant for: Janssen, D. Sholter: None declared, M. Starr Consultant for: Janssen, A. Masetto: None declared, J. Sampalis Shareholder of: JSS Medical Research, Employee of: JSS Medical Research, E. Rampakakis Employee of: JSS Medical Research, C. Tkaczyk Employee of: Janssen, M. Shawi Employee of: Janssen, A. Lehman Employee of: Janssen, F. Nantel Employee of: Janssen, S. Otawa Employee of: Janssen